A Fast Non-Contact Imaging Photoplethysmography Method Using a Tissue-like Model - McDuff, Daniel; Blackford, Ethan B.; Estepp, Justin R.; Nishidate, Izumi (SPIE BiOS, 2018, 2018)
Imaging photoplethysmography (iPPG) allows non-contact, concomitant measurement and visualization of peripheral blood flow using just an RGB camera. Most iPPG methods require a window of temporal data and complex computation, this makes real-time measurement and spatial visualization impossible. We present a fast,“window-less”, non-contact imaging photoplethysmography method, based on a tissue-like model of the skin, that allows accurate measurement of heart rate and heart rate variability parameters. The error in heart rate estimates is equivalent to state-of-the-art techniques and computation is much faster.